Technology and Music - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers are introduced to a host of ways to make music with the help of technology - - Learn about synthesizers, samplers, MIDI, and recording techniques - - See how the famous rock group, The Hooters, works at a recording session - - Hear how sounds can be digitally processed.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - Questions to Encourage Critical Thinking - - Correlations with THE MUSIC CONNECTION - - Vocabulary ? Student Follow-up - -Music Contents - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: MIDI (Standard).; Synthesizer (Musical instrument).; Electronic musical instruments; Films for the hearing impaired